The First Freshmen Students’ University Test of English Proficiency: A Descriptive and Correlational Study - Prasodjo, Pandu; Sally, Sally (Lingual Journal of Language and Culture; Vol 14 No 2 (2022): Lingual: Journal of Language and CultureDO - 10.24843/LJLC.2022.v14.i02.p01, 2022)
Listening and reading play an essential role in students learning English as a foreign language. Recognizing freshmen students’ English language proficiency through the University Test of English Proficiency (UTEP) helps the university to portray the batch performance and decide future policies and teaching strategies for the English lesson. This is important for the EFL teachers developing teaching strategies that are suitable for students. However, a study to describe the current phenomena of the first freshmen students and the existence of the relationship between UTEP listening and reading proficiency scores also needed to be conducted for the sake of UTEP's continuous improvement as an assessment instrument. Therefore, the present study aims to (1) investigate the descriptive statistics of the current batch first UTEP; and (2) find out the existing relationship between freshmen students’ UTEP reading and listening proficiency scores. A quantitative method was applied to describe the current UTEP scores statistically and to find out the degree of correlation coefficient of freshmen students’ first UTEP. The data was collected from 863 freshmen students who took their first UTEP and statistically analyzed using SPSS version 26. The results revealed that there is a positive and quite strong relationship between freshmen students’ UTEP reading and listening proficiency scores. Finally, this report could be used for further consideration for stakeholders in developing teaching strategies for the batch and evaluating the current UTEP for encouraging better tests and continuous improvement to enhance graduates’ English language proficiency and accomplish the expected output.